Mucinous adenocarcinoma with signet ring cell features of the sublingual gland: A case report with an immunohistochemical analysis. Issue 3 (May 2018) - Nagata, Masashi; Kusafuka, Kimihide; Yoshida, Ryoji; Kawahara, Kenta; Nakagawa, Yoshihiro; Nakamoto, Masafumi; Shinohara, Masanori; Nakayama, Hideki
Abstract: Mucinous adenocarcinoma (MAC) is a highly aggressive tumor, and its origin in the salivary glands is extremely rare. We report one case of salivary MAC showing highly invasive features with signet ring cells and immunohistochemical analysis. A 77-year-old Japanese woman who noticed painless swelling of the right floor of the mouth received surgical treatment and was diagnosed with primary MAC of the sublingual gland. The tumor consisted of two components: a glandular pattern and diffuse pattern with large mucinous lakes containing numerous signet ring cells. The tumor cells were immunopositive for CEA, CA125 and CK7 and strongly positive for Her-2 but negative for CK20, androgen receptor, GCDFP-15 and p63. The prognosis was poor, and the patient developed peritoneal metastasis and died. This case suggests that signet ring cell features in MAC may be a phenotype of aggression, and Her-2 may be a therapeutic target for MAC.